Self-recovery of chiral microphase separation in an achiral diblock copolymer system. Issue 7 (17th January 2023) - Miao, Tengfei; Cheng, Xiaoxiao; Zhang, Gong; Wang, Yuqing; He, Zixiang; Wang, Zhao; Zhang, Wei
Abstract : A chirality-storing copolymer MPS structure will overcome the external chiral source dependence and avoid tedious synthesis and expensive raw materials. Abstract : Macroscopic regulation of chiral supramolecular nanostructures in liquid-crystalline block copolymers is of great significance in photonics and nanotechnology. Although fabricating helical phase structures via chiral doping and microphase separation has been widely reported, the chiral memory and self-recovery capacity of asymmetric phase structures are the major challenge and still deeply rely on the presence of chiral additives. Herein, we demonstrate the first controllable chiral microphase separation in an achiral amphiphilic block copolymer consisting of poly(ethylene oxide) and azobenzene (Azo) groups. Chirality can be transferred to the fabricated helical nanostructures by doping with chiral additives (tartaric acid, TA). After the removal of the chiral additives and then performing cross-linking, the formed helical nanostructures will completely dispense with the chiral source. The supramolecular chirality and the micron-scale phase structure can be maintained under UV irradiation and heating-cooling treatment, enabling a reversible "on–off" chiroptical switch feature. This work is expected to avoid the tedious synthesis and expensive raw materials and shows a great application prospect in chiral separation and so on.